(untitled) (Research, Society and Development, 2022)
The pandemic caused by the SARS-CoV-2 virus brought damages to the mental health of individuals. In this context, the present work consists of the evaluation of the repercussions of the pandemic related to the mental health of the medical students at an institution in the Brazilian Midwest. Thus, a questionnaire composed of sociodemographic questions and technical questionnaires, PHQ-9 (Patient Health Questionnaire), SRQ-20 (Self-Reporting Questionnaire) and ASSIST/WHO (Alcohol, Smoking and Substance Involvement Screening Test), was applied to the students between June and September 2022. This is a cross-sectional, descriptive study, with a quantitative and prospective approach. Students from the first to the ninth period answered the survey, 69.9% were female, 86.5% were in their first undergraduate course, and 90.2% did not work. Regarding the changes related to the pandemic, 52.8% had changes in weight, 67.9% had no previous diagnosis of psychological disorder, 28.0% had a diagnosis of anxiety disorder and 12.4% of depression. 81.3% reported changes in interpersonal relationships, 38.3% had family loss due to COVID-19, and 37.3% for another reason. 21.2% have or had suicidal ideation, 9.3% attend NAPSI (Núcleo de Apoio Psicossocial), and 32.6% are monitored by an outside psychologist. According to the PHQ-9, 34.1% of the participants have a possible diagnosis of major depression. With the SRQ-20, 55.4% were identified as having a possible common mental disorder. Finally, the ASSIST/WHO identified alcohol as the most used substance, with 32.6% using it weekly. Therefore, a probable psychic suffering of the students related to the pandemic is noted.